2019
DOI: 10.1002/ptr.6476
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Cornus mas fruit extract consumption on lipid profile, glycemic indices, and leptin in postmenopausal women— A randomized clinical trial

Abstract: Menopause, which occurs following a declined ovarian activity and reduced estrogen levels, can lead to long‐term changes in lipid and glycemic profiles and increases the risk of cardiovascular disease and osteoporosis. Cornelian cherry (Cornus mas) is rich in phytochemicals and antioxidants, which appears to be useful in reducing the postmenopausal complications. This interventional, double‐blinded, randomized clinical trial carried out on 84 menopaused women aged 45–60 years old. They were randomly divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 36 publications
1
24
0
2
Order By: Relevance
“…The lipid‐lowering effect of cornelian cherries may be due to their impact on glucose metabolism. Both animal and human studies have shown that supplementation with cornelian cherries can be an effective means of reducing blood glucose levels in those with hyperglycemia (Gholamrezayi et al., 2019 ; Soltani et al, 2015 ), increasing insulin sensitivity and improving insulin resistance (Gholamrezayi et al., 2019 ). Based on the observed results, it has been proposed that insulin resistance of the adipocytes can cause an increase in the release of fatty acids into the circulation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lipid‐lowering effect of cornelian cherries may be due to their impact on glucose metabolism. Both animal and human studies have shown that supplementation with cornelian cherries can be an effective means of reducing blood glucose levels in those with hyperglycemia (Gholamrezayi et al., 2019 ; Soltani et al, 2015 ), increasing insulin sensitivity and improving insulin resistance (Gholamrezayi et al., 2019 ). Based on the observed results, it has been proposed that insulin resistance of the adipocytes can cause an increase in the release of fatty acids into the circulation.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, the decrease in blood glucose levels leads to an increase in the concentration of cyclic AMP, which reduces the TG concentration in the blood (Sutherland & Robison, 1969 ; Wu et al, 2012 ). Hence, considering the valuable role of cornelian cherries in glucose homeostasis, it has been suggested that supplementation with this kind of cherry may reduce blood serum levels of triglycerides (Gholamrezayi et al., 2019 ; Soltani et al, 2015 ). Cornelian cherries are known to contain a range of phytochemicals, such as anthocyanins, flavonoids, phenolic acids, and tannins (Milenković‐Anđelković et al, 2015 ), which may exhibit inhibitory activities on HMG‐CoA reductase through their ability to bind and inactivate enzymes (Ademosun et al., 2015 ; Baskaran et al., 2015 ; Lee et al., 2003 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yukarıda bahsedilen biyoaktif bileşenler dışında, yüksek oranda C vitamini içermekte olan bu gruptaki meyveler, β karoten, A vitamini, E vitamini ile potasyum başta olmak üzere mineral açısından da oldukça zenginlerdir 23,36,37 39,40,42,[48][49][50] , anti-inflamatuar 43,44,[46][47][48][49] , anti diyabetik 54,55 , hipolipidemik 16,[53][54][55] , artrit ve endotelyal disfonksiyon 43,57,58 ile hipertansiyon [60][61][62] üzerine pozitif etki…”
Section: Flavonoid Ve Flavanollerunclassified
“…Dislipideminin vasküler bütünlüğü, yapısını ve fonksiyonunu bozabileceği gösterilmiştir16 . Kiraz grubu kırmızı meyvelerin yüksek antioksidan ve anti-inflamatuar etkilerinden dolayı DM hastalığı ve lipid bozukluklarını iyileştirmede etkin oldukları düşünülmektedir16,[53][54][55] . Jafari ve ark.,53 2008 yılındaki çalışmalarında T2DM hastası olan 19 kadın bireyde 6 hafta 400 ml vişne suyu takviyesinin açlık kan şekerini %8 oranında; vücut ağırlığı, kan basıncı, hemoglobin A1c (HbA1c), total kolesterol (TC) ve yüksek yoğunluklu lipoprotein (LDL) seviyelerinde azalmaya yol açtığını göstermişlerdir.…”
unclassified